Safety of Intra‐Amniotic and Intra‐Fetal Digoxin Administration in Late Second‐Trimester Abortion by Dilation and Evacuation - Eleanor A. Drey; Nora Goldschlager; Neal L. Benowitz; Abby Sokoloff; Rebecca A. Jackson (Perspectives on Sexual and Reproductive Health, 2026)
ABSTRACT Objective The study's purpose was to determine the safety of two routes and doses of digoxin through assessment of systemic absorption, cardiac rhythm, and coagulation parameters injected as part of second‐trimester dilation and evacuation abortion. Methods We randomized pregnant women between 19 and 23 weeks' gestation to receive either 1.5 mg digoxin through intra‐amniotic injection (IAI) or 1.0 mg through intrathoracic injection (IFI). We measured subjects' serum digoxin levels and coagulation indices over 48 h post‐injection and cardiac rhythm monitoring for 24 h. Results Ten patients in each group completed the study. All injections caused fetal demise within 24 h. In the IAI group, mean (±SD) digoxin peak concentration in the IAI group was 1.5. ±0.72 (range 0.7–2.9 ng/mL); in the IFI group 1.4 ± 0.74 ng/mL (range 0.5–2.4 ng/mL). Mean (±SD) time to peak digoxin level in the IAI group was 10.7 ± 8.5 h (range, 1–24 h); in the IFI group 1.5 ± 0.97 h (range, 1–4 h, p < 0.01). Five patients had laboratory‐defined critical digoxin levels of uncertain significance. Cardiac rhythm monitoring showed no digoxin‐associated rhythm or conduction abnormalities. Prothrombin and partial thromboplastin time levels remained normal in both groups. Conclusion Neither 1.5 mg IAI nor 1.0 mg IFI of digoxin administered to induce fetal demise was associated with adverse maternal cardiac outcomes or coagulation parameter changes. Serum levels reflected significant digoxin absorption in both groups, generally resulting in maximum digoxin concentration peaks in the low therapeutic range. Injecting digoxin to cause fetal demise in abortion care appears safe and effective.